Media Effects in the Viewer's Choice Era: Testing Revised Agenda-Setting and Priming Hypotheses. (4th May 2021) - Lau, Richard R.; Rogers, Kathleen; Love, Jamel
ABSTRACT: One of the not-so-minimal effects of media exposure is the ability of the media to set the agenda for political discussion and debate, to tell voters what to think about, if not what to think. Most experimental studies of agenda-setting probably over-estimate its actual effects, however, by forcing exposure to a story on some particular topic – an especially unrealistic setting in today's viewer's choice media environment. We avoid this problem by exploring agenda-setting and priming in a more realistic campaign environment, a 10-wave panel study where we randomly varied the opportunity to learn particular policy stands from competing gubernatorial, House, and Senate candidates in a mock off-year election campaign. We find correlational evidence that explicit attention to stories about a particular political issue is associated with greater perceived importance of that issue, but random assignment of exposure to such stories has no causal effect on perceived importance. We find weak evidence that agenda-setting is limited to in-party partisans.